Application of Power Point Media Towards Increasing Learning Outcome of Class IV Students on Thematic Learning at SDN Kemuning - Dian Nur Antika Eky Hastuti (Green Publisher Indonesia, 2021)
This study aims to determine the application of Power Point media to fourth grade students in thematic learning at SDN Kemuning, to determine the improvement of fourth grade student learning outcomes to the application of power point media in thematic learning at SDN Kemuning and to determine the response of fourth grade students to the application of Power point media. Point on thematic learning at SDN Kemuning. This research is a Classroom Action Research (CAR) which was carried out in two cycles. The subjects of the research were the fourth grade elementary school students with 20 students consisting of 10 male students and 10 female students. The results of this study indicate that the application of power point in thematic learning can increase the learning interest of fourth grade students at SDN Kemuning. It is proven that students are more enthusiastic in listening, paying attention and asking researchers. Meanwhile, the learning outcomes of fourth grade students at SDN Kemuning can be seen from the average posttest score and the percentage of complete learning. In the first cycle, 16 students who got a score of 75 with a learning completeness of 90%. In the second cycle, 18 students who got a score of 75 with a learning completeness of 95%. Student responses to the application of Power Point media in thematic learning indicate that students are happy with the application of this media and through the application of this Power Point media students can more easily understand the material presented by the teacher.